Investigation of Metastable Zone Width and Nucleation Kinetics of 2-cyanoguanidine by Cooling Crystallization - Ning Zhang (Science Faculty of Chiang Mai University, 2019)
Metastable zone widths (MSZW) of 2-cyanoguanidine in water, methanol, and ethanol are determined at different cooling rates ((6-30) K×h-1) using polythermal method, respectively. The metastable zone widths of solute in the three solvents increase linearly with the cooling rate increasing. Three nucleation theories are employed to estimate nucleation kinetic parameters based on measured MSZW data. The apparent nucleation order m is computed by Self-consistent Nývlt-like approach and Kubota’s model, which suggests that the nuclei are formed by instantaneous nucleation in methanol and ethanol, while the 2-cyanoguanidine nucleate in water shows the occurrence of progressive nucleation mechanism. The activation energy Esat for nucleation of crystals in solution also is estimated by Arrhenius-type equation.